A bioactivity guided study on the antibacterial activity of Hertia cheirifolia L. extracts. (May 2017) - Majouli, Kaouther; Hamdi, Assia; Msaada, Kamel; Kenani, Abderraouf
Abstract: This study was carried out with the objective to investigate the antibacterial activity of Hertia cheirifolia L. extracts against Gram-positive and Gram-negative strains including Staphylococcus aureus (ATCC 6538), Bacillus subtilis (ATCC 6633), Bacillus licheniformis, Esherichia coli (ATCC 8739), Pseudomonas aeruginosa (ATCC 9027), Salmonella enterica (CIP 8039) and Salmonella typhimirium . The results of this antibacterial screening showed that the ethyl acetate (EtOAc) extracts had the best activity against the tested microorganisms. A bioassay-oriented fractionation approach for the more active extract (roots ethyl acetate extract) led to the obtaining five sub-fractions. Furthermore, these sub-fractions were also tested for antimicrobial activity and the best results were obtained for the roots EtOAc sub-fraction (C) with MICs values between 0.039 and 0.156 mg/mL. Reversed-phase high performance liquid chromatography (RP-HPLC) analysis indicated that the major phenolic components of active (EtOAc) extracts and sub-fraction (C) are fisetin hydrate (82.06%), trans cinnamic acid (63.66%), gallic acid (38.97%) and myricetin (20.92%). These results may help to improve these natural antibacterial substances that could serve as selective agents for bacterial diseases. Highlights: Antibacterial activity screening of H. cheirifolia extracts against some Gram + and Gram − strains. Bioassy-guided fractionation of the roots ethyl acetate extract. The identification and quantification of phenolic compounds of ethyl acetate extracts from H. cheirifolia.